PEMBUATAN ALAT PENGERING KERUPUK UNTUK INDUSTRI KECIL PEDESAAN - Wibowo, Heri; Purnomo, Edy (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The problems faced by crisply industry "Sarinah" was the problem of dryer of kerecek (raw crisply) which need wide of place and very depend on weather. The operation could be adapted by requirement of good production on noon or night. Target activity of this program was give additional aid of equipment of production matching with requirement of small industry so that production mount and have technology mainstay production, efficient and cheap of operating expenses.To overcome problems of production draining of crisply, gone through the following stages: (1) making scheme of crisply dryer according to requirement of small industry; (2) making crisply dryer with adequate capacities (15.000-20.000) in a short times (7 - 8 hours), and (3) partner industry can exploit dryer technology in an optimal flashing.Execution of activity orients on efficacy of making of dryer able tobe exploited properly. The result of make-up of small industrial productivity after wearing this appliance is marked with attainment of larger ones om set. Total the omset before this program is 8000 crisply sold (equivalent of Rp800.000,00/day). After adjustment of technology of dryer, tired mean omset13.000 until 15.000 crisply. On bad weather, industrial this crisply produces crisply till 20.000 because getting the order 5000 of crisply from other industries. This means program of this voucher can increase product on small industry. Key words: dryer, crisply, small industrial